Web-Based Boarding House Management Information System with Payment Gateway Integration - Ketut Arya Wisnu Wardana; Tri Widodo (International Journal of Science and Environment (IJSE), 2026)
Manual management at GreenKost in Sleman faces challenges in unstructured recording of room, tenant, and financial transaction data, along with slow and error-prone administrative processes. This study aims to develop a web-based boarding house management information system with Model-View-Controller (MVC) architecture using Laravel framework to optimize business processes and improve tenant services. The research methodology includes direct observation on February 17, 2025, and interviews with the boarding house owner on February 25, 2025, to identify system requirements. The system was developed using Laravel 12.x with MySQL database and Eloquent ORM, integrated with a payment gateway to support QRIS and E-Wallet payments. Main features include user management, room management with real-time status, online reservation and booking, integrated payments, admin dashboard reports, announcement management, and repair request services. Testing using black-box testing method shows all features function as expected under both normal and abnormal conditions. The research results demonstrate that an integrated digital system can automate payment verification, improve administrative efficiency, and provide ease of information access and real-time transactions for tenants.